Quantum Thermodynamics: The Second Law in the Quantum World - David Miller; Robert Harris; Yulia Ivanova (Yayasan Adra Karima Hubbi, 2025)
The second law of thermodynamics is one of the basic principles of physics that applies in the classical and quantum worlds. Although this principle is widely accepted, its application in quantum systems is still the subject of intense research. This research focuses on the application of the second law of thermodynamics in the quantum world, with an emphasis on the influence of quantum entanglement on entropy and energy changes in quantum systems. The purpose of this study is to explore how the second law of thermodynamics applies in quantum systems and how quantum entanglement affects the rate of entropic change. This study aims to identify the differences between quantum systems and classical systems in the context of thermodynamics. This study uses experimental and simulation methods on simple quantum systems, such as trapped ions, to measure changes in entropy as temperature increases. The data obtained were analyzed to identify the influence of quantum entanglement on the rate of entropy change and how this differs from classical systems. The results showed that quantum entanglement affected the rate of entropy increase, with quantum systems showing slower entropy changes compared to classical systems. This suggests that entropy in quantum systems is not only affected by temperature, but also by quantum interactions between particles. This study concludes that the second law of thermodynamics remains valid in the quantum world, but with significant modifications due to the influence of quantum entanglement. These findings pave the way for the development of more complex and applicable quantum thermodynamic models, which can be used in the design of future quantum technologies.